Dabigatran etexilate and concomitant use of non-steroidal anti-inflammatory drugs or acetylsalicylic acid in patients undergoing total hip and total knee arthroplasty: No increased risk of bleeding - Friedman, Richard J.; Kurth, Andreas A.; Clemens, Andreas; Noack, Herbert; Eriksson, Bengt I.; Caprini, Joseph A. (Thrombosis and Haemostasis, 2012)
Patients undergoing total hip or knee arthroplasty should receive anticoagulant therapy because of the high risk of venous thromboembolism. However, many are already taking non-steroidal anti-inflammatory drugs (NSAIDs) or acetylsalicylic acid (ASA) that can have antihaemostatic effects. We assessed the bleeding risk in patients treated with thromboprophylactic dabigatran etexilate, with and without concomitant NSAID or ASA. A post-hoc analysis was undertaken of the pooled data from trials comparing dabigatran etexilate (220 mg and 150 mg once daily) and enoxaparin. Major bleeding event (MBE) rates were determined and odds ratios (ORs) generated for patients who received study treatment plus NSAID (half-life ≤12 hours) or ASA (≤160 mg/day) versus study treatment alone. Relative risks were calculated for comparisons between treatments. Overall, 4,405/8,135 patients (54.1%) received concomitant NSAID and 386/8,135 (4.7%) received ASA.ORs for the comparison with/without concomitant NSAID were 1.05 (95% confidence interval [CI] 0.55–2.01) for 220 mg dabigatran etexilate; 1.19 (0.55–2.55) for 150 mg; and 1.32 (0.67–2.57) for enoxaparin. ORs for the comparison with/without ASA were 1.14 (0.26–5.03); 1.64 (0.36–7.49); and 2.57 (0.83–7.94), respectively. For both NSAIDs and ASA there was no significant difference in bleeding between patients with and without concomitant therapy in any treatment arm. Patients concomitantly taking NSAIDs or ASA have a similar risk of MBE to those taking dabigatran etexilate alone. No significant differences in MBE were detected between dabigatran etexilate and enoxaparin within comedication subgroups, suggesting that no increased major bleeding risk exists when dabigatran etexilate is administered with NSAID or ASA.Investigation performed at multiple centres participating in the RE-MODEL™, RE-NOVATE®, and RE-MOBILIZE® trials.
Keywords: Oral; dabigatran etexilate; non-steroidal anti-inflammatory drugs; ASA; bleeding